Human educational trajectory in the XXI century: the influence of behavioral factors (Regional aspects of productive forces development of Ukraine, 2020)
The article analyzes the current trends of the global and domestic market of online education. It is established that the modern market of online education is characterized by the active development of micro-learning; promotion of mobile learning; the use of artificial intelligence in EdTech; the close link between training and employment; increasing the target market for companies working in the direction of career-long learning; demand for practices of mutual, or cross-learning, (p2p-learning); leading positions of educational companies in the development of modern EdTech; low prevalence of virtual and augmented reality (AR and VR) in the development of online education; ineffective use of gamification in online education; the popularity of project-based learning; the close connection of online learning with talent development practices; growth of the LMS market (learning management systems); sustainable growth of the corporate segment of online education; the spread of more innovative educational practices than asynchronous (self-paced) learning.Modern incentives for the development of the online education market in Ukraine are highlighted: outdated educational base, military conflict in eastern Ukraine, recognition by some universities of distance learning as a separate form of education, development of Internet technologies, changing qualification requirements in the labor market, reducing the value of traditional education. the role of universities in the socialization of individuals, the lack of territorial affiliation, the introduction of quarantine measures.The priority directions of construction of the educational trajectory of the person are generalized and the influence of behavioral factors on it is determined. It was found that the key aspects that individuals focus on when building an educational trajectory are: the desire to quickly enter the labor market, spreading the practice of mastering lucrative professions without significant material and time costs for training, increasing educational opportunities through the introduction of distance learning abroad and domestic institutions. It is proved that behavioral factors have a significant impact on determining the educational trajectory of a person. Therefore, the identification and regulation of such influences accelerates the effective adaptation of man to the changing conditions of the labor market and the market of educational services, as well as allows to effectively build and adjust its educational trajectories.